(3GdOdGdGJ aj CMcGe GdfLhes
(3ChdgG (B:s
(3GdebGdI GdChdi gi YTQI aUhd GdChd ai PcQ UhQI GdLfjf hJOHjQ GdchGcH dg ef hbJ SbhWg ai GdQMe Edi hbJ hdGOJg Edi ePgH GdCFeI GdeJbOejf , hQCi GdMceGA GdeJCNQjf s
(3BNQgG (B:s
(3hai (B12 (3jbd CYOGDg hjLgQhf HGdYOGhI hjSde ef TQge hajeG PcQfG caGjI hGddg CYde bO Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs